HLA-DRB and HLA-DQB Allele and Haplotype Frequencies in Iranian Patients with Recurrent Aphthous Stomatitis - Najafi, Shamsolmoulouk; Mohammadzadeh, Mahsa; Zare Bidoki, Alireza; Meighani, Ghasem; Aslani, Saeed; Mahmoudi, Mahdi; Rezaei, Nima (Iranian journal of allergy, asthma, and immunology, 2016)
Recurrent aphthous stomatitis (RAS) is known as the most common chronic disease of the oral cavity, which affects a range of 5-25% of the population. RAS appears to be associated with some human leukocyte antigen (HLA) class II alleles and haplotypes. This study attempts to survey the distribution of HLA-DRB and -DQB alleles among Iranian RAS patients and healthy controls. In order to evaluate the association of HLA-DR and DQ alleles and haplotypes, 54 patients with RAS and 100 unrelated healthy subjects as control group were investigated. Our data indicated that DRB1*13:17, DRB1*15:01, and DRB5*01 were significantly more frequent in RAS patients in comparison to controls. However, DRB3:01allele frequency was higher in the controls compared to the patients. The significantly frequent allele in the patients compared with the healthy subjects was HLA-DQB1*03:02. However, both HLA-DQB1*02:01 and HLA-DQB1*03:01 alleles were most frequent in the healthy individuals rather than the patients. The DRB*04/DQB1*03:01 and DRB*01:01/DQB1*02:01 haplotypes were significantly distributed in healthy subjects compared with patients. However, DRB*07:01/DQB1*03:02 haplotype was found to be significantly frequent in patients than controls. In respect of HLA genes, factors are involved in the incidence of RAS; various HLA-DRB and HLA-DQB1 alleles and the related haplotypes are suggested to be the three main RAS susceptibility factors in our population study.